Adsorption du chrome par une hydroxyapatite à base de test d’oursin Paracentrotus lividus (Lamarck 1816) - NEGGAZ, Fayza (My University, 2020)
The release of heavy metals into the environment poses major problems for ecosystems and human health. Among the solutions proposed, absorption technologies appear particularly promising. The aim of this study is to evaluate the adsorption force of the composite material, namely hydroxyapatite from the sea urchin test (Paracentrotus lividus) with chemical treatment followed by thermal activation according to a metal removal protocol. heavy (chrome) well defined. Our study was carried out by modifying the values of temperature, initial pH, amount of adsorbent, initial concentration and contact time to remove heavy metal ions from the aqueous solution. We did not have the opportunity to complete the practical part because of the Coronavirus. We only compared the results of others.
Keywords: Heavy metals; Adsorption; Hydroxyapatite; Urchin Paracentrotus lividus